The Implementation of Discovery Learning Method to Increase Learning Outcomes and Motivation of Student in Senior High School - Saridewi, Nanda; Suryadi, Joko; Hikmah, Nur (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract Based on data from the observation of high school students grade XI that daily low student test scores due to a lack of role of students in the learning process. This classroom action research aims to improve learning outcomes and student motivation through discovery learning method in colloidal material. This study uses the approach developed by Lewin consisting of planning, action, observation, and reflection. Data collection techniques used the questionnaires and ability tests end. Based on the research that results for students received a positive influence on learning by discovery learning model by increasing the average value of 74 students from the first cycle to 90.3 in the second cycle and increased student motivation in the form of two statements based competence (KD) categories (sometimes) on the first cycle and the first statement KD category in the second cycle. Thus the results of this study can be used to improve learning outcomes and student motivation. Keywords: Discovery Learning Method, Learning Outcomes, Student Motivation, Colloid